Male antennae of Armadillidium vulgare discriminate Wolbachia-infected females - Mouret, Nicolas; Tolassy, Vincent; Richard, Freddie-Jeanne (Comptes rendus. Chimie, 2023)
In natural populations of A. vulgare , the endosymbiont Wolbachia feminizes genetic males. When confronted with genetic females and feminized males, males prefer genetic females. We tested whether the ability of males to discriminate both females involved the detection of chemical compounds by extracting female cuticular compounds through various solvent baths and presenting them to male antennae. We also tested female antennae responses to evaluate the potential impact of Wolbachia on individual detection. Our results showed that only the ethyl acetate extracts triggered a significantly different response of male antennae between the two types of females. No difference between female antennal detection was recorded. Further experiments are required to identify the involved molecule explaining the sexual preference of males towards Wolbachia -free females.